Analisis Kebutuhan Air Irigasi Di Desa Pagar Banyu Kecamatan Pagar Alam Utara - Elpita Aisah (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2019)
The overall need for irrigation water needs to be known as it is one of the important stages required in the planning and management of irrigation systems. Based on this, the purpose of this research is to analyze the irrigation water requirement in the study area of ​​Irrigation Area of ​​Pagar Banyu Village, Pagar Alam Utara Subdistrict, for Irrigation Area of ​​Pagar Banyu Village with an area of ​​26 ha, the source of water comes from Pagar Banyu water siring. Factors for determining irrigation water requirements include land preparation, consumptive use, percolation and seepage, effective change of water layer and rainfall. The calculation is done manually with the concept of KP-01. The need for irrigation water starts from the beginning of November using the rice-rice-palawija cropping pattern. From the total calculation, the irrigation water demand is 1.02 m3 / dt, while the available water discharge in Pagar Banyu is 1.37m3 / st, thus it can be concluded that the available water can meet the irrigation water needs in the irrigation area of ​​Pagar banyu Village Kecamtan Northern nature fence.